Towards a Multimodal Hermeneutic Model: The case of Uber-Blog-mediated advertising discourse order of ‘Saudization’ - Amir H.Y. Salama (Russian Journal of Linguistics, 2023)
This study proposes a Multimodal Hermeneutic Model (for short, MHM) as a methodology that extends the analytic scope of Ricoeur’s (1973, 1976, 1981) classic hermeneutic theory of text interpretation towards examining multimodal texts. The model has been empirically tested by examining the advertising discourse order of ‘Saudization’ as channelled via the Saudi Uber Blog’s multimodal text. A twofold social semiotic praxis has been theoretically incorporated into the distanciation-appropriation dialectics underlying the interpretation of multimodal texts in potentia . First, a multimodal cluster transcription (Baldry Thibault 2006) has been utilized in enhancing the description of distanciated text sense as a holistic configuration of clusters across different communicative modalities with interacting semiotic modes ( intra-textually ). Second, an interpersonal-meaning analysis of multimodal participants (Kress Van Leeuwen 2006a, 2006b, Halliday Matthiessen 2004) has been employed in enriching the explanation of appropriated text reference ( extra-textually ). The empirical site used for validating the MHM is the Uber-Blog-mediated multimodal text designed by Saudi Arabia-based Uber Company. The multimodal transcription of textual clusters has demonstrated how the text sense thematically revolves around the macro topic of ‘Saudization’ across verbal, visual, and pictorial modalities with material and semiotic modes, viz. linguistic, graphological, anthropic, sartorial, spatial, natural, and technological. The multimodal participant analysis has explained how the referents of (i) a model Saudi Uber driver, (ii) the Saudi Public Transport Authority, (iii) Saudi driver-partners, and (iv) Uber app collectively contribute to the recontextualization of ‘Saudization’ from a governmental discourse to an advertising discourse order realized in the multimodal text under analysis.